PROGNOSTIC VALUE OF TUMOR MARKERS KI67 AND P53 IN DETECTING RECURRENCE OF BLADDER CANCER (Western European Journal of Medicine and Medical Science, 2024)
Bladder cancer (BC) remains one of the predominant pathologies in onco-urological practice and poses a significant challenge for global healthcare. Understanding the risk factors and prognosis of this disease can improve prevention, early detection, and treatment of this type of cancer.